Training Assessment of Palestinian Contractors - Adnan Enshassi; Kamalain Shaath (Journal of Construction in Developing Countries, 2007)
The construction industry is the instrument through which urbanization is undertaken. As it is generally recognized as the major locomotive, the construction industry sets the tone for the national economy. In recent months, the construction activities have increased considerably and several major housing and infrastructure projects are now under way both in the West Bank and Gaza. The purpose of this paper is to evaluate a training programme, which is conducted in the Gaza Strip for Palestinian contractors. The primary purpose of the programme was to improve management and increase productivity of existing small scale construction enterprises in Palestine. An assessment of Improve Your Construction Business (IYCB) is made. The qualitative research of interviewing was used in this study. This has been conducted by reviewing project documents, reports, publications and interviewing all the project's stakeholders, at the institutional level as well as the level of the intended direct and indirect beneficiaries. The paper concludes with a set of findings and recommendations in order to supply the necessary feedback and information needed to assess and possibly revise policies, strategies, objectives, institutional arrangements and resources.